2010
DOI: 10.1590/s1980-65232010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Stress levels and quality of sleep in subjects with temporomandibular joint dysfunction

Abstract: Purpose: The aim of this study was to test the association between quality of sleep and stress in individuals with temporomandibular disorder (TMD).Methods: The study sample consisted of 354 adult subjects (males and females) from the municipality of Piacatu, São Paulo state, in the Southeast region of Brazil. Data were collected using the Fonseca's Questionnaire to record the level of TMD, the Pittsburgh Sleep Quality Index (PSQI) to assess quality of sleep and the Social Readjustment Rating Scale (SRRS) to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 11 publications
2
20
1
5
Order By: Relevance
“…26 Poor sleep quality or insomnia in turn, are directly related to increased anxiety, leading to the development of a vicious cycle, with sleep pattern changes and increased oral parafunction. 15 About 70% to 80% of people diagnosed with sleep bruxism present symptoms of fragmented sleep, moderate to intense daytime sleepiness, nonrestorative sleep, nighttime arousals, sudoresis, or nightmares. 5,19,27 Corroborating this statement, in the present study, of the 45 individuals who experienced SB, 75.6% (34) considered their sleep as poor quality, and only 11 (24.4%) participants were classified as having a good pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Poor sleep quality or insomnia in turn, are directly related to increased anxiety, leading to the development of a vicious cycle, with sleep pattern changes and increased oral parafunction. 15 About 70% to 80% of people diagnosed with sleep bruxism present symptoms of fragmented sleep, moderate to intense daytime sleepiness, nonrestorative sleep, nighttime arousals, sudoresis, or nightmares. 5,19,27 Corroborating this statement, in the present study, of the 45 individuals who experienced SB, 75.6% (34) considered their sleep as poor quality, and only 11 (24.4%) participants were classified as having a good pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of these 7 components results in an index which may vary from 0 to 21 points. 14,15 Scores above 5 points are indicative of a poor quality sleep pattern, 15,16 thus allowing the standard classification as ''good'' or ''bad. ''…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have found that multiple factors can lead to the development of this disorder and that it is therefore caused by an association of psychological, structural and behavioral factors 2,4 .…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of the population with some form of TMD is between 40 and 60% 4,5 . According to Fonseca et al 6 , it was estimated that in Brazil, there are approximately six million individuals with signs and symptoms of TMD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation